2010
DOI: 10.1212/wnl.0b013e3181cef85d
|View full text |Cite
|
Sign up to set email alerts
|

How preserved is episodic memory in behavioral variant frontotemporal dementia?

Abstract: Objective: Studies have shown variable memory performance in patients with behavioral variant frontotemporal dementia (bvFTD). Our study investigated whether this variability is due to the admixture of patients with true bvFTD and phenocopy patients. We also sought to compare performance of patients with bvFTD and patients with Alzheimer disease (AD). Methods:We analyzed neuropsychological memory performance in patients with a clinical diagnosis of bvFTD divided into those who progressed (n ϭ 50) and those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
121
3
13

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 190 publications
(154 citation statements)
references
References 37 publications
17
121
3
13
Order By: Relevance
“…Furthermore, bvFTD and AD patients differed on the memory scores with more severe impairment in AD. This replicates our previous findings [2] which also showed a similar "step-function" of bvFTD and AD memory performance with bvFTD patients showing a lesser memory impairment than AD. Prior studies [19] showed an even milder memory impairment in bvFTD, which might have been due to the inclusion of so called phenocopy cases, who generally do not show memory impairments [2].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, bvFTD and AD patients differed on the memory scores with more severe impairment in AD. This replicates our previous findings [2] which also showed a similar "step-function" of bvFTD and AD memory performance with bvFTD patients showing a lesser memory impairment than AD. Prior studies [19] showed an even milder memory impairment in bvFTD, which might have been due to the inclusion of so called phenocopy cases, who generally do not show memory impairments [2].…”
Section: Discussionsupporting
confidence: 92%
“…This replicates our previous findings [2] which also showed a similar "step-function" of bvFTD and AD memory performance with bvFTD patients showing a lesser memory impairment than AD. Prior studies [19] showed an even milder memory impairment in bvFTD, which might have been due to the inclusion of so called phenocopy cases, who generally do not show memory impairments [2]. Phenocopy cases mimic the behavioral symptoms of bvFTD but do not progress in their disease, show no macroscopic brain atrophy, and perform at control level for most neuropsychological tests.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations